2015
DOI: 10.1586/14737175.2015.1065180
|View full text |Cite
|
Sign up to set email alerts
|

Effects of antiepileptic drugs on interictal epileptiform discharges in focal epilepsies: an update on current evidence

Abstract: Interictal epileptiform discharges (IEDs), occurring in the electroencephalograms (EEG) of patients with focal epilepsy, are crucial for diagnosis, while their relationship with seizure severity and recurrence is controversial. The effects of antiepileptic drugs (AEDs) on IEDs are even more debated. In general, it is currently believed by experts in the field that most of the classical AEDs do not significantly affect IEDs occurrence in these patients, and that monitoring their EEG effects during treatment is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 69 publications
2
14
0
Order By: Relevance
“…[6][7][8][9][10][11][12][13][14][15][16] More specifically, the confounding factors that influence the diag- with AEEG. [27][28][29] Three dogs in our population received 4 to 6 ASD (1 dog received These data support further questions about the potential use of AEEG as a monitoring tool for epileptic patients. However, levetiracetam previously has been shown to decrease ictal epileptiform discharges in a Rhodesian ridgebacks with juvenile myoclonic epilepsy and absence seizures.…”
Section: Discussionsupporting
confidence: 70%
“…[6][7][8][9][10][11][12][13][14][15][16] More specifically, the confounding factors that influence the diag- with AEEG. [27][28][29] Three dogs in our population received 4 to 6 ASD (1 dog received These data support further questions about the potential use of AEEG as a monitoring tool for epileptic patients. However, levetiracetam previously has been shown to decrease ictal epileptiform discharges in a Rhodesian ridgebacks with juvenile myoclonic epilepsy and absence seizures.…”
Section: Discussionsupporting
confidence: 70%
“…48,49 Recently, Guida et al published a review of past studies that sought to determine the effects of AEDs (alone or in combination) on focal IEDs and concluded that the data is scarce or conflicting for classical AEDs and absent or limited for newer AEDs. 50 In any case, they considered their findings consistent with the prevailing view that focal IEDs are not influenced by chronic AED therapy in patients with focal epilepsy. There are few reports of successful control of PLEDs using carbamazepine, midazolam, pentobarbital, sodium valproate, and felbamate, 22 but these studies must be replicated.…”
Section: Discussionmentioning
confidence: 59%
“…Future work is also needed to more fully characterize the behavior during GEDs using automatic real‐time detection algorithms, which might succeed in attaining faster and more consistent rates of stimulus presentation than we achieved with human visual review. Another factor that could be investigated with a larger sample size is potential effects of antiseizure medications, which are known to influence epileptiform discharges and might also affect behavior …”
Section: Discussionmentioning
confidence: 99%